2014
DOI: 10.1515/secm-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fly ash particles on tensile and impact behaviour of aluminium (Al/3Cu/8.5Si) metal matrix composites

Abstract: The present work aimed to study the tensile and impact behaviour of fly ash particle reinforced aluminium matrix composites. Fly ash particles reinforced aluminium (Al/3Cu/8.5Si) matrix composites were fabricated by the stir casting technique. Three different size ranges of fly ash particles (50–75, 75–103 and 103–150 μm) were used. The composites were subjected to tensile and impact tests. The tensile and impact fracture surfaces of the aluminium alloy and composites were investigated using a scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…It is also a typical brittle fracture, and the crack is mainly generated at the corner of the coarse Chinese character eutectic Fe 2 Nb phase, as shown in figure 14(d). The current results align with Samal et al [37] and Kumar et al [39].…”
Section: Metallographic Characterization Of Al-5cu-2ni-xfenb Compositessupporting
confidence: 93%
See 1 more Smart Citation
“…It is also a typical brittle fracture, and the crack is mainly generated at the corner of the coarse Chinese character eutectic Fe 2 Nb phase, as shown in figure 14(d). The current results align with Samal et al [37] and Kumar et al [39].…”
Section: Metallographic Characterization Of Al-5cu-2ni-xfenb Compositessupporting
confidence: 93%
“…Ravikumar et al [28] observed that impact strength reduces with an increasing fraction of tungsten carbide reinforcements in AA6082 alloy. Similar outcomes were reported by other researchers [38,39]. The impact strength of the composites may be enhanced by a secondary process of fabrication such as hot forging [37].…”
Section: Mechanical Characterization Of Al-5cu-2ni-xfenb Compositessupporting
confidence: 88%
“…Kok et al [ 28 ] have reported about the effect of Al 2 O 3 particle dispersions in the matrix, the Al 2 O 3 particles with 32 μm particle size had better strength characteristics as compared to 16 μm particle dispersions in the matrix, which is in line with the findings of the present work, viz., the strength increases with the increase in size of inoculant particles. Kumar et al [ 29 ] have reported the findings related to the influence of fly ash reinforcements on the tensile strength of Al/3Cu/8.5Si and have drawn similar inferences of increase in the strength with the increase in wt. % of fly ash attributed to close packing of the reinforcements in the matrix.…”
Section: Resultsmentioning
confidence: 79%
“…The comparative evaluation of the ultimate tensile strength of the composite specimens for different compositions of the reinforcements and heat treatment temperatures is given in Figures 9-12. From the graph (Figure 9), it is evident that the ultimate tensile strength of the composites increases with the increase in the wt.% of fly ash due to inoculation accelerated by the thermal exposure of the composites in the post-treatment condition up to a temperature of 160 • C, as ascertained by the findings of the Kumar et al [36], who reported the findings related to the influence of fly ash reinforcements on the tensile strength of Al/3Cu/8.5Si and drew similar inferences of increase in the strength with the increase in wt.% of fly ash attributed to close packing of the reinforcements in the matrix. However, the increase in the thermal exposure temperature to 200 • C leads to a slight decrease in the ultimate tensile strength which can be attributed to the agglomeration of the reinforcements at certain regions in the matrix at an elevated temperature of exposure, as reported in the findings of Kok et al [37] about the effect of thermal exposure on the Al 2 O 3 particle dispersions in the matrix; the Al 2 O 3 particles dispersed in the matrix phase and exposed to a temperature of 150 • C had better strength characteristics, as compared to those aluminium composites with Al 2 O 3 particle dispersions in the matrix subjected to a temperature above 150 • C which is in line with the findings of the present work.…”
Section: Ultimate Tensile Strength (Uts)mentioning
confidence: 76%